The influence of islamic financial literacy on students’ interest in investing in the islamic capital market with the use of the Islamic online trading system as an intervening variable - Diyah, Berliany Sulingga Caesar Mustikaning; Sholikha, Akhris Fuadatis (Journal of Entrepreneurial Economics, 2025)
Background: The rapid advancement of technology has significantly influenced financial literacy and infrastructure, which are essential for effective financial management. Technological progress has also reshaped investor behavior in managing investment portfolios. Islamic financial literacy plays a crucial role in shaping students’ interest in investment. Additionally, the Islamic online trading system serves as an essential platform that facilitates investment activities. Previous studies have emphasized the importance of financial literacy in investment decisions, but there is a need to examine how Islamic financial literacy interacts with online trading platforms in influencing students’ investment interest. Methods: This study employs a quantitative research approach. The sample was selected using incidental sampling, and data were collected through questionnaires. The data were analyzed using path analysis to determine the direct and indirect effects of Islamic financial literacy on students' investment interest, with the Islamic online trading system as a mediating variable. Findings: The findings indicate that Islamic financial literacy significantly influences the use of the Islamic online trading system. Furthermore, Islamic financial literacy has a direct and significant effect on students' investment interest. The results also show that the use of the Islamic online trading system significantly impacts students’ interest in investing in the Islamic capital market. Additionally, the study confirms that Islamic financial literacy indirectly affects investment interest through the mediating role of the Islamic online trading system. Conclusion: Islamic financial literacy is a critical factor that enhances students' interest in investing in the Islamic capital market, both directly and through the use of the Islamic online trading system. These findings highlight the importance of integrating financial education and digital platforms to foster greater participation in Sharia-compliant investments. Novelty/Originality of this article: This study contributes to the existing literature by examining the mediating role of the Islamic online trading system in the relationship between Islamic financial literacy and students’ investment interest. The findings provide new insights into the impact of digital financial platforms on investment behavior, particularly within the context of Islamic finance.